Switzerland-wide Neospora caninum seroprevalence in female cattle and identification of risk factors for infection - Gliga, Diana S.; Basso, Walter; Ardüser, Flurin; Moore-Jones, Gaia; Schares, Gereon; Zanolari, Patrik; Frey, Caroline F. (Frontiers in Veterinary Science, 2022)
Neospora caninum is an important cause of abortion in cattle worldwide. Infection in cattle occurs horizontally by ingestion of oocysts shed by canids or vertically, from an infected dam to the fetus, and may result in abortion, stillbirth, or birth of seropositive offspring. The control of bovine neosporosis is difficult and costly. The objectives of this study were to estimate the current nationwide seroprevalence of N. caninum infections in Swiss cattle and to assess risk factors for infection with this parasite. We conducted a cross-sectional study with cattle farms randomly selected and stratified according to population size, resulting in a sample of 780 female cattle. The cattle originated from 161 farms distributed over all Switzerland. The serum samples were tested for antibodies against N. caninum using a commercial ELISA and if inconclusive, retested using an in-house immunoblot technique. To collect farm parameters relevant to N. caninum transmission and prevention, farm owners were mailed a questionnaire which addressed topics putatively related to N. caninum infection such as husbandry, history of abortion, and presence of dogs on farm. Univariate analysis by generalized linear mixed model (with animal seropositivity as outcome variable) and logistic regression modelling (with farm seropositivity as outcome variable) was conducted on farm parameters investigated in the questionnaire. By ELISA and immunoblot, 4.2% (33/780) of cattle sera yielded positive results. At the farm level, 16.2% (26/161) of the sampled farms had at least one seropositive animal. The return rate of the valid questionnaires was 54.0%. At the animal level, odds for farm seropositivity were 3.8 times higher when rodents had been recorded by the farmer as a problem on the farm. At the farm-level, two protective factors were identified: rearing of replacement heifers and feeding of concentrated feed. We recorded a low seroprevalence of N. caninum in a random sample of Swiss cattle representative for the years 2017-2018. Based on a questionnaire survey, we could identify risk and protective factors for infection with N. caninum, however these need to be confirmed in further studies.